2004
DOI: 10.1152/ajpheart.00061.2004
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y antagonism reduces reflex cutaneous vasoconstriction in humans

Abstract: Previous studies have provided evidence of a non-noradrenergic contributor to reflex cutaneous vasoconstriction in humans but did not identify the transmitter responsible. To test whether neuropeptide Y (NPY) has a role, in two series of experiments we slowly reduced whole body skin temperature (TSK) from 34.5 to 31.7 degrees C. In protocol 1, Ringer solution and the NPY receptor antagonist BIBP-3226 alone were delivered intradermally via microdialysis. In protocol 2, yohimbine plus propranolol (Yoh + Pro), Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 36 publications
4
91
1
Order By: Relevance
“…The finding that the combination of ice or LA with fiber placement reverses the increased threshold is not in keeping with this speculation about damage to nerve fibers by fiber placement. The finding that fiber placement increases the threshold for activation of the active vasodilator system to a higher temperature might also be due to fiber placement disrupting local transmitters, such as substance P (34) or others (4,17,20,25,32,33). It could also be that the elevated levels of histamine observed in the first 30 min following fiber placement (7) lead to its depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that the combination of ice or LA with fiber placement reverses the increased threshold is not in keeping with this speculation about damage to nerve fibers by fiber placement. The finding that fiber placement increases the threshold for activation of the active vasodilator system to a higher temperature might also be due to fiber placement disrupting local transmitters, such as substance P (34) or others (4,17,20,25,32,33). It could also be that the elevated levels of histamine observed in the first 30 min following fiber placement (7) lead to its depletion.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that this combination and level of adrenergic antagonists was effective in inhibiting the cutaneous vascular responses to exogenous norepinephrine (36 -37, 39). Subjects had two microdialysis probes placed intradermally (3,7,20,39). These probes, described previously (3,7,20), consisted of 1 cm of microdialysis tubing (inner diameter 200 m, 18 kDa nominal molecular weight cutoff) attached at each end to polyimide tubing.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…1). Finally, norepinephrine (10 mM) was perfused through the microdialysis tubing to the sites to test for the adequacy of blockade (39). A reduction in CVC at a yohimbinepropranolol-treated site of Ͼ10% was taken to indicate inadequate blockade, and data from any such site were excluded from further analysis.…”
Section: Methods and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations